REMOVAL OF COD, BOD, AMMONIA AND TSS USING ELECTROCOAGULATION METHOD WITH A COMBINATION OF ALUMINUM (Al) AND IRON (Fe) ELECTRODES IN FISH PROCESSING WASTEWATER - Munawarah, Syahna; Juliansyah Harahap; Rohendi, Aulia (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
The Wastewater from fish processing contains highly organic pollutants, causing pollution to water bodies. Electrocoagulation method is utilised in fisheries wastewater treatment because of its simple and easier to do and also effective in removing pollutants. This research uses an experimental method with a quantitative approach by using dependent variables such as COD, BOD, ammonia, TSS and pH and independent variables such as electrical voltage of 3, 5 volts and contact time of 60, 90 and 120 minutes. The results of the electrocoagulation process using Al and Fe electrodes showed the effectiveness of reducing the concentration of COD, BOD and TSS values ​​by 96.34%, 95.2% and 73.22% with the maximum voltage of 5 volts and a contact time of 120 minutes. The effectiveness of reducing ammonia concentration occured at the optimum voltage of 3 with a contact time of 60 minutes, which was 98.75%. The pH concentration increased from acidic to alkaline. Based on the results of this study, the amount of voltage in the electrocoagulation method can affect the concentration of COD, BOD, ammonia and TSS contained in wastewater from fish processing. The results obtained show the quality of wastewater in accordance with predetermined quality standards.